2014
DOI: 10.1044/1059-0889(2013/11-0031)
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning From Bimodal to Bilateral Cochlear Implant Listening: Speech Recognition and Localization in Four Individuals

Abstract: Purpose The use of bilateral stimulation is becoming common for cochlear implant (CI) recipients, with either a CI in one ear and a hearing aid (HA) in the non-implanted ear (CI&HA - bimodal) or CIs in both ears (CI&CI - bilateral). The objective of this study was to evaluate performance of four individuals who transitioned from bimodal to bilateral stimulation. Methods Participants had completed a larger study of bimodal hearing and subsequently received a second CI. Test procedures from the bimodal study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 53 publications
(88 reference statements)
4
21
1
Order By: Relevance
“…For example, if a person uses a CI and a contralateral hearing aid and there is minimal contribution of the hearing aid to the binaural score, bilateral CIs could be the next step. Indeed, studies conducted by Ching et al (2007) and Potts and Litovsky (2014) have reported on these client outcomes comparing bimodal to bilateral CI use, with encouraging results.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, if a person uses a CI and a contralateral hearing aid and there is minimal contribution of the hearing aid to the binaural score, bilateral CIs could be the next step. Indeed, studies conducted by Ching et al (2007) and Potts and Litovsky (2014) have reported on these client outcomes comparing bimodal to bilateral CI use, with encouraging results.…”
Section: Discussionmentioning
confidence: 95%
“…For these reasons, bimodal users may be at a further disadvantage compared to bilateral CI users on sound localization tasks. Studies comparing sound localization ability across these modes within a given individual have shown that bilateral CI use provides improved sound localization and better subjective outcomes compared to bimodal use for adult listeners (Ching et al, 2007; Potts & Litovsky, 2014), suggesting that, at least for some individuals, bilateral CI use may provide better spatial hearing ability than bimodal use.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, deaf patients wearing bilateral cochlear implants can detect ILDs (Nopp et al . ; van Hoesel, ; Seeber & Fastl, ; Potts & Litovsky, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, OTOF patients with cochlear implants might be able to process ILDs efficiently. Indeed, deaf patients wearing bilateral cochlear implants can detect ILDs (Nopp et al 2004;van Hoesel, 2004;Seeber & Fastl, 2008;Potts & Litovsky, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Potts and Litovksy 13 describe speech understanding and sound source localization for four individuals in bimodal and bilateral CI conditions. The individuals received little benefit from amplification in the bimodal condition, as scores were no different than the unilateral CI condition.…”
Section: Introductionmentioning
confidence: 99%